The ethical dimension of travel agencies business in changing business environment (Serbia) – employees’ attitudes vs. employees’ conduct expected by management - Simat, Karolina; Dragin, Aleksandra; Pavlukovic, Vanja; Markov, Slobodanka (Geographica Pannonica, 2019)
The purpose of the paper is to provide an empirical study of employees’ ethical behavior in travel and tourism industry. A survey research was done in 2012 in the Republic of Serbia among employees in travel agencies as one of the most important subjects in heterogeneous structure of travel and tourism industry, using a questionnaire designed according to the basic theoretical principles of professional ethics. Dealing with the issue of ethical responsibility of employees in travel agencies, this work examines whether employees have business ethics awareness and what kind of individual and corporate social responsibility as part of business environment is undertaken in this regard. The findings of the study showed that employees of travel agencies are ready to act in an ethical manner, although it is the opposite of management attitudes in specific situations. Finally, the paper provides a critical evaluation of entrepreneurial activities and obstacles that travel agencies encounter while operating in the Serbian economy in transition.